A study on Idiomatic expressions containing the word “eye” in English with reference to their Vietnamese equivalents / DƯƠNG THỊ HƯƠNG THÚY; NHDKH Dang Ngoc Huong, Ph.D - DƯƠNG, THỊ HƯƠNG THÚY
My graduation thesis namely “Idiomatic expressions containing the word “eye” in English with reference to their Vietnamese equivalents” involves the contrastive study of the syntactic and semantic features of idioms containing words containing the word eye in English and Vietnamese. In order to achieve the aims given, the major method to be employed in the study is a descriptive one, analysis method and survey method. This can surely help teachers anticipate problems in the lessons and seek the possible solutions to solve these problems. Therefore, the considerations, remarks, consumptions, comments and conclusions in the thesis are mainly based on data analysis. A number of data relating to idiomatic expressions containing the word “eye” in both English and Vietnamese publications are collected from textbooks, short stories, books on English and Vietnamese languages. They are then analyzed in the light of cross- cultural perspective and analysis. Data collected will then be analyzed in order to find out the similarities and differences between English and Vietnamese idiomatic expressions containing the word “eye”.